Thermodynamic calculation of intermetallic compounds in AZ91 alloy containing calcium - 吴玉锋 杜文博 聂祚仁 曹林锋 左铁镛 (Transactions of Nonferrous Metals Society of China, 2006)
Based on the Miedema model and Chou model, the activities of different solute components in Mg-Al-Zn, Mg-Ca-Zn and Mg-Al-Ca ternary systems were calculated. The results show that the variety of zinc content has little influence on the activity of Al or Ca, and the interaction of Zn and Al or Ca can be neglected when the mass fraction of Zn is lower than 2% in the AZ91 alloy containing calcium （noted as Mg-Al-Zn-Ca system）. Therefore, the possible intermetallic compounds in the Mg-Al-Zn-Ca system can be predicted by directly calculating the Gibbs flee energies of the reactions in Mg-Al-Ca system. The calculated Gibbs flee energies in the Mg-Al-Ca system indicate that Al2Ca phase can take priority of depositing, which agrees with the experimental results in references. The consistency of calculation and experiment proves that the intermetallic compounds in the Mg-Al-Zn-Ca system can be predicted by the Miedema model and Chou model.